Family Governance Signals and Heterogeneous Preferences of Investors. Issue 4 (2nd October 2018) - Duncan, Keith; Hasso, Tim
ABSTRACT: The authors explore if investors use signals of founding family governance (ownership, involvement in management, board representation) when making investment choices in an experimental setting. The authors link the literature on heterogeneous preferences of investors to signaling theory, and apply it in the context of founding family governance by exploring the presence of investor clusters with varying utility functions with respect to founding family governance. The authors show that nonprofessional investors use these signals in their investment choices. Latent class analysis identifies 3 distinct clusters within our sample that have conflicting utility curves with respect to founding family governance.